A neonatal large neck lymphatic malformation successfully treated with Eppikajyutsuto - Shunsuke Watanabe; Yusuke Funato; Masafumi Miyata; Tatsuya Suzuki (Elsevier, 2022)
Currently, there are various treatment methods for neck lymphatic malformations (LMs). In recent years, there have been reports of usage of Eppikajyutsuto (TJ-28), a traditional Japanese Kampo medicine for LMs. We report the case of a patient who was delivered art 38 weeks and 5 days of gestation, with a birth weight of 3958 g. A right neck cyst was identified during the fetal period. Contrast-enhanced CT and cytology revealed a right large neck LM (14.0 × 11.7 × 6.0 cm) after birth by cesarean delivery. First, we considered sclerotherapy and mTOR inhibitors because of the necessity to reduce the tumor size however, it was thought that there might be complications associated with their usage. Hence, TJ-28 was administered at 39 days of age. A sufficient tumor shrinkage effect was observed 3 months after administration, and therefore, surgical resection was performed 8 months after administration. TJ-28 is considered to be a useful treatment with few side effects for large neck LMs when sclerotherapy or mTOR inhibitors are contraindicated in patients.